2017
DOI: 10.7567/jjap.56.022401
|View full text |Cite
|
Sign up to set email alerts
|

Introduction effects of three electron-withdrawing groups into bis-styrylbenzene skeleton on photoelectric and photophysical properties

Abstract: I synthesized three bis-styrylbenzene derivatives substituted with typical electron-withdrawing groups: E,E-1,4-bis(4-trifluoromethystyryl)benzene (CF3), E,E-1,4-bis(4-cyanostyryl)benzene (CN), and E,E-1,4-bis(4-nitrostyryl)benzene (NO2). The photophysical and photoelectrical properties of these compounds were evaluated in detail. In free molecules in the solution, the intramolecular charge transfer interaction appeared in NO2. In the solid state of CN, the intermolecular charge transfer interaction was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The as-evaporated 4Be4CN lm showed a monomodal and wide uorescence spectrum due to its intermolecular charge transfer interaction. 26 However, the uorescence spectrum of the as-evaporated 3Be4CN lm was similar to that obtained in solution, suggesting that 3Be4CN shows no intermolecular charge transfer interaction. The absorption edges of the as-evaporated Th4CN, Py4CN and 3Be4CN lms, determined from the excitation spectra, were 517, 418, and 374 nm, respectively, and these were shied to longer wavelengths by 61, 26, and 14 nm, respectively, from the absorption edges in their solutions.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…The as-evaporated 4Be4CN lm showed a monomodal and wide uorescence spectrum due to its intermolecular charge transfer interaction. 26 However, the uorescence spectrum of the as-evaporated 3Be4CN lm was similar to that obtained in solution, suggesting that 3Be4CN shows no intermolecular charge transfer interaction. The absorption edges of the as-evaporated Th4CN, Py4CN and 3Be4CN lms, determined from the excitation spectra, were 517, 418, and 374 nm, respectively, and these were shied to longer wavelengths by 61, 26, and 14 nm, respectively, from the absorption edges in their solutions.…”
Section: Resultsmentioning
confidence: 69%
“…Table 2 shows that the IP values of the three compounds studied decreased in the order of Th4CN (−5.94 eV) > 3Be4CN (−6.53 eV) > Py4CN (−6.62 eV). Introduction of the CN group lowered the IP value, and thus, the IP value of 4Be4CN was −6.09 eV, 26 suggesting that the V-shaped structure of 3Be4CN is more susceptible to the effect of the CN group than the linear 4Be4CN molecule. The IP value of Py4CN was −6.62 eV, higher than that of 3Be4CN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of several π-conjugated oligomers has contributed to the advancement of organic optical and electronic devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, bis-styrylbenzene derivatives (BSDs) and thiophene/phenylene co-oligomers (TPCOs) show remarkable optical and electrical characteristics. Various studies have reported the excellent photophysical properties of BSDs and TPCOs, where 1,4-bis(4trifluoromethylstyryl)benzene and α,ω-bis(biphenylyl) terthiophene (BP3T) show very low amplified spontaneous emission thresholds.…”
Section: Introductionmentioning
confidence: 99%